The macroeconomic pattern of natural disasters (2004)
Notes that hurricanes have a definite economic and, more precisely, macroeconomic pattern in terms of their impact and effects. States that the estimation of the financing gap, and the orientation and specific objectives of the reconstruction process are two important issues related to the macroeconomic impact of natural disasters and their aftermath.
Keywords: NATURAL DISASTERS